Effects of Bureucratic Reformation Implementation on Service Recipients Satisfaction at PSPA Satria, PSMP Antasena, and BBRSBD Prof Dr Soeharso - Muhtar Muhtar (Jurnal Penelitian Kesejahteraan Sosial, 2014)
The aim of this study is to know the satisfaction of service recipients in PSPA Satria, PSMP Antasena, and BBRSBD Prof Dr Soeharso. Type of the study is qualitative-descriptive, using collecting data technique: interviews, group discussions, questioner distribution, observation, and documentary analysis. Informants are leaders of technical service units and representatives of employees (structural, functional), including service beneficiaries as respondents. The three technical services unit as the locations of study are PSPA Satria, PSMP Antasena, and BBRSBD Prof Dr Soeharso. The result of the study shows that the quality of services in PSPA Satria is â€œvery goodâ€, and â€œgoodâ€ in two others -PSMP Antasena and BBRSBD Prof Dr Soeharso-. To improve the quality of public services, is suggested to improve communication, adequate resources, commitment to program implementers, and bureaucratic structures which are based on standard operating procedures that govern the flow of work and the implementation of the policy.